Situational context and public perceptions of officer appearance: A vignette-based study of police uniforms and accouterments - Simpson, Rylan (Criminology & criminal justice, 2025)
Previous research has documented the effects of uniforms and accouterments on public perceptions of police in acontextual settings. Drawing upon a vignette-based survey, we explored the perceptual effects of various police uniforms and accouterments in the context of five different policing environments: (1) a burglary where the suspect was present, (2) a burglary where the suspect was not present, (3) a foot patrol, (4) a roadblock, and (5) a siege involving a barricaded person. As part of our research design, a sample of Queensland adults (N = 292) rated images of police officers from the Queensland Police Service in different aesthetic capacities in each aforementioned environment along three perceptual outcomes: (1) traits, (2) effectiveness, and (3) procedural justice. The analyses reveal that appearance manipulations can impact public perceptions of officers. The analyses also indicate that the effects of some manipulations can sometimes vary by situational context. We discuss our results with respect to past and future research as well as operational policing practices.